2015
DOI: 10.1111/pce.12536
|View full text |Cite
|
Sign up to set email alerts
|

Jasmonoyl isoleucine accumulation is needed for abscisic acid build‐up in roots of Arabidopsis under water stress conditions

Abstract: Phytohormones are central players in sensing and signalling numerous environmental conditions like drought. In this work, hormone profiling together with gene expression of key enzymes involved in abscisic acid (ABA) and jasmonate biosynthesis were studied in desiccating Arabidopsis roots. Jasmonic acid (JA) content transiently increased after stress imposition whereas progressive and concomitant ABA and Jasmonoyl Isoleucine (JA-Ile) accumulations were detected. Molecular data suggest that, at least, part of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
84
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 113 publications
(88 citation statements)
references
References 41 publications
3
84
0
1
Order By: Relevance
“…7 In a previous publication it was shown that jasmonates and in particular Jasmonic acid Isoleucine (JA-Ile) accumulation and, hence JA-dependent signaling, was necessary for consistent ABA accumulation in roots of Arabidopsis. 8 Although plants defective in JA-Ile accumulation (jar1-1) and JA-Ile dependent signaling (coi1-16) were able to accumulate ABA in roots after dehydration, accumulation was significantly lower compared to their respective WT. Interestingly, in complementary experiments using the same system, JA transiently accumulates in roots of dehydrated plants but this increase is coupled with a decrease in the hormone concentration in shoots.…”
mentioning
confidence: 99%
“…7 In a previous publication it was shown that jasmonates and in particular Jasmonic acid Isoleucine (JA-Ile) accumulation and, hence JA-dependent signaling, was necessary for consistent ABA accumulation in roots of Arabidopsis. 8 Although plants defective in JA-Ile accumulation (jar1-1) and JA-Ile dependent signaling (coi1-16) were able to accumulate ABA in roots after dehydration, accumulation was significantly lower compared to their respective WT. Interestingly, in complementary experiments using the same system, JA transiently accumulates in roots of dehydrated plants but this increase is coupled with a decrease in the hormone concentration in shoots.…”
mentioning
confidence: 99%
“…A central molecule is 13-hydroperoxy octadecatrienoic acid (13-HPOT) that can be further metabolized into 13-keto octadecatrienoic acid, cleaved into n-hexenal, or diverted into jasmonate biosynthetic pathway (Schaller, 2001). Besides jasmonates that do have a role in stress responses (De Ollas et al, 2015), fatty acid hydroperoxides have been shown to have a role in the induction of HR after pathogen attack (Dat et al, 2005;Zoeller et al, 2012) although cell death is not always associated with lipid peroxidation (Dat et al, 2005). In animal systems, lipid signaling plays an important role in the development of inflammatory response.…”
Section: Phytoalexinsmentioning
confidence: 99%
“…Citrus produce a large number of triterpenoids that have been associated to fruit and juice quality as well as responses of vegetative tissues to the environment. These compounds are synthesized from squalene by formation of a polycyclic molecule containing a furanolactone core structure; the main representative is limonin and its respective glucosylated form (Arbona et al, 2015). These compounds have been found to accumulate in vegetative Citrus tissues in response to HLB and could be part of the metabolic defense response (Manthey, 2008;Slisz et al, 2012).…”
Section: Phytoalexinsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the assumption that the existence of tRNA-Ile is related to the presence of isoleucine in cells, Mayer et al (1990) showed that the rate of isoleucine synthesis increased up to 6-fold in cowpea plants under heat shock conditions. Also, it has been found that the presence of compounds such as jasmo-noyl-isoleucine is required to synthesize abscisic acid (ABA) in Arabidopsis thaliana roots under drought stress conditions (Ollas et al, 2015). ABA is a growth regulator which is known to be responsive to osmotic and cold stresses in plants (Ishitani et al, 1997).…”
Section: Sequence Analysis Of Differentially Displayed Cdna Fragmentsmentioning
confidence: 99%